Civilization issues of deliberations on a man in the conception of Erazm Majewski - Bukowska, Sonia (Folia Philosophica, 2017)
The subject of the article is the concept of a man formed by a Polish philosopher and sociologist Erazm Majewski (1858—1922). The appropriate topic of the deliberations is preceded by a short reflection concerning the area of anthropological inquiry in the beginning of the 20th century. The analysis of Erazm Majewski’s views raises the question of a research perspective established by the philosopher, and then the possibility to obtain an answer to the question of human nature on basis of the theory of civilization. A special attention was paid the premises, which as defined by Majewski, enabled a man to cross the borders of the animal world.